A Rare Case of Superior Mesenteric Artery Thrombosis in Multiple Myeloma - Jasminder Singh; Kusum Yadav; Ankush Kaushik; Irshad Babu (Journal of Applied Hematology)
Superior mesenteric artery (SMA) thrombosis is a life-threatening illness which results in bowel ischemia due to compromised blood supply to small bowel along with proximal colon. A 60-year-old male presented with symptoms of dull aching diffuse type of abdominal pain associated with vomiting, diarrhea, and fever. His clinical examination was unremarkable. His hemoglobin levels were low with markedly raised erythrocyte sedimentation rate and alkaline phosphatase levels. On diagnostic evaluation, he was found to have multiple myeloma with SMA thrombosis associated with bowel ischemia and sepsis. This case report emphasizes the importance to rule out the possibility of plasma cell dyscrasias in elderly patients presenting with clinical features of mesenteric artery thrombosis.